Domestic Science Class - Frank Aston::::::photographer:::
Domestic science classes at the Polytechnic School included bookkeeping and mathematics as well as cooking and sewing. Cooking classes were so successful that local residents visited campus for meals. Merchant A. Z. Sinsheimer wrote to his wife in May 1914: "[Daughter] Gertrude and I will probably go to the Poly tomorrow, and I am for partaking of the lunch prepared by the pupils."